Impact of aerosol enclosure barrier to videolaryngoscopic oro-tracheal intubation: A pilot manikin study. Issue 1 (January 2021) - Hui, Chun Fai; Li, Alex; Wong, Chi Keung Gordon
Background: Personal protective equipment used for protection of healthcare workers in the combat against Severe Acute Respiratory Syndrome Coronavirus 2 pandemic is in limited supply worldwide at present – 2020. Use of barrier enclosure during endotracheal intubation can potentially act as a cost-effective adjunct to minimize risks of transmitting the infection to healthcare workers. However, there is concern that the enclosure itself will act as a barrier to the intubation procedure in the emergency settings. Objective: To evaluate the negative effect of barrier enclosure (an aerosol box) on the performance of video-assisted intubation in a manikin Methods: A total of 41 Emergency Department doctors from a local hospital were recruited to perform intubation in a manikin simulating normal and more difficult airways (Cormack-Lehane grades I and IIb) with and without the box. The primary outcome was time of successful intubation. The secondary outcomes were first-attempt success rate, number of successful attempts, need of adjuncts, dental injury and ease of intubation as perceived by the participants. Results: The aerosol box had no significant negative effect on the time of successful intubation (p = 0.630 (Grade I airway) and p = 0.436 (Grade IIb airway)), first-attempt success rate, number of successful attempts, need of adjuncts or dental injury. Participants subjectively reported extra yet minor challenges during intubation in the presence of the box. Conclusion: Within limits of the pilot study, the aerosol box had no statistical significant difference but an increasing trend of prolonged endotracheal intubation interval in the Grade IIb airway and negative impact on first-pass success, and could potentially be used to protect healthcare workers during the aerosol-generating intubation procedure.